SAT0316 Relationship of ultrasonographic measurement of osteophytes and femoral cartilage thickness to radiographic severity of knee osteoarthritis. (23rd January 2014) - Mathiessen, A.; Haugen, I.K.; Robinson, P.S.; Engen, C.N.; Østerås, N.; Engebretsen, L.; Kvien, T.K.; Hammer, H.B.
Abstract : Background: Conventional radiography is the main outcome measure in epidemiological studies of osteoarthritis (OA), but the use of ultrasound (US) has gained increased interest with ability to visualize both osteophytes and soft tissue structures. Objectives: To explore the relationship between ultrasonographic features of knee OA (osteophytes and femoral cartilage thickness) and degrees of radiographic knee OA. Methods: We included 234 participants (160 women, mean (SD) age 64.4 (8.7) years) from the MUST study ("the Musculoskeletal pain in Ullensaker Study"), which is a population-based study of persons with self-reported OA of the knee, hand and/or hip joints. The US examination included assessment of femoral and tibial osteophytes (grade 0-3) in the medial and lateral compartments using longitudinal scan positions on extended knees, and measure of femoral cartilage thickness (millimetres) at the medial and lateral condyles and in the notch with the probe transversely at the distal femur with knee in maximum flexion (5-13 MHz probe, Siemens Antares). The highest osteophyte score and lowest cartilage thickness in each knee was used in our analysis. Radiographs were read using the Kellgren-Lawrence (KL) scale (0-4). We calculated the prevalence of osteophytes and the mean (SD) cartilage thickness in knees with no OA (KL grade 0), doubtful (KL grade 1), mild (KL grade 2) and moderate/severe OA (KL grade ≥3). KL grades 3 and 4 were evaluated together due to few joints in each category (n=44 and n=7, respectively). Results: Fifty-eight joints were excluded due to knee replacement or amputation. In 410 assessed knee joints, the prevalence and severity of US osteophytes increased with radiographic severity (table). A high proportion of US osteophytes were also found in joints with no/doubtful OA (KL ≤1). We did not find lower cartilage thickness with increasing radiographic severity (table). Conclusions: This study demonstrates a clear relationship between US detected osteophyte scores and increased radiographic severity of OA, but no association between femoral cartilage thickness and radiographic OA was found. The results indicate that US examination of osteophytes may be useful in the clinical setting for evaluation of knee OA, but the validity and usefulness of US in measuring cartilage thickness in knees may be questioned. Disclosure of Interest: None Declared